Exploring Saudi EFL Learners’ Perceptions and Use of AIPowered English Language Learning Platforms in the Context of Vision 2030 - Rami Mubarak (European Scientific Journal, ESJ, 2025)
The given study talks about how Saudi EFL students perceive and use AI-based learning tools in English language classes based on the technology acceptance model (TAM) and Saudi Vision 2030. A quantitative descriptive approach was employed in the collection of data through an online questionnaire that was sent to 68 Saudi undergraduate students studying in Saudi public universities who were males. As the results have shown, the level of awareness of AI tools was very high (83.8%), and the most used platforms were ChatGPT, Duolingo, and Grammarly. Students displayed fairly favourable attitudes concerning the usefulness of AI and the benefits of engagement, but reported difficulties associated with overdependence, privacy benefits, and a lack of Arabic compatibility. Overall, the results demonstrate a balanced optimism and propose institutional policies, ethical education, and AI literacy to facilitate successful implementation in Saudi higher education.